Genomic and genetic advances of oiltea-camellia (Camellia oleifera) - Ye, Changrong; He, Zhilong; Peng, Jiayu; Wang, Rui; Wang, Xiangnan; Fu, Mengjiao; Zhang, Ying; Wang, Ai; Liu, Zhixian; Jia, Gaofeng; Chen, Yongzhong; Tian, Bingchuan (Frontiers in Plant Science, 2023)
Oiltea-camellia (C. oleifera) is a widely cultivated woody oil crop in Southern China and Southeast Asia. The genome of oiltea-camellia was very complex and not well explored. Recently, genomes of three oiltea-camellia species were sequenced and assembled, multi-omic studies of oiltea-camellia were carried out and provided a better understanding of this important woody oil crop. In this review, we summarized the recent assembly of the reference genomes of oiltea-camellia, genes related to economic traits (flowering, photosynthesis, yield and oil component), disease resistance (anthracnose) and environmental stress tolerances (drought, cold, heat and nutrient deficiency). We also discussed future directions of integrating multiple omics for evaluating genetic resources and mining key genes of important traits, and the application of new molecular breeding and gene editing technologies to accelerate the breeding process of oiltea-camellia.